Coaching to support men in making informed choices about prostate cancer screening: A qualitative study. Issue 5 (May 2018) - Ilic, Dragan; Murphy, Kerry; Collins, Veronica; Holden, Carol
Highlights: General practitioners have limited opportunity to engage in shared decision making. Decision coaching may facilitate informed patient decision making. Perceived barriers to decision coaching include time, resources and cost. Abstract: Objective: The objective of this study was to examine the perceptions of men, practice nurses (PNs) and general practitioners (GPs) on patient decision coaching for prostate cancer screening. Methods: Seven focus groups were conducted with 47 participants, representing three stakeholder groups − men, GPs and PNs. All focus group discussions were conducted by the same facilitator and guided by a semi-structured interview schedule. Transcriptions were analysed by thematic analysis. Results: Knowledge about the merits of prostate cancer screening was high amongst GPs, but limited with PNs and men. All groups saw the value in PN-led decision coaching for men considering screening for prostate cancer, but had reservations about its implementation in practice. Barriers to implementing a decision coaching system with PNs included staffing and cost of implementation. Conclusion: GPs, PNs and men identified benefits for the use of a PN-led decision coaching support intervention to assist men with making an informed choice about screening for prostate cancer. Stakeholders had reservations about how a PN-led intervention would effectively work in clinical practice. Practice implications: A feasibility study is required to examine barriers and enablers to implementing a PN-led decision coaching process for prostate cancer screening in the Australian primary healthcare setting.